[KCPR DJ Scott Cody at console] (1998)
KCPR DJ Scott Cody (aka "Tom Collins") in the KCPR studio. Scott Cody was the Alumni Coordinator and Air Staff Instructor for KCPR. Together with Andrew Patterson (aka "Dr. Martin Rossi") he ran a show on KCPR called "Shaken, Not Stirred," playing swing and lounge music.